Effects of Downhill Running Exercise on Glucose Tolerance and Skeletal Muscle P-AMPK Expression in Type II Diabetes Rats - Sung-Tae Park (Asian Society of Kinesiology, 2022)
OBJECTIVES The purpose of this study was to investigate the effects of moderate downhill running exercise on glucose tolerance and skeletal muscle phospho-AMP activated protein kinase(P-AMPK) expression in type Ⅱ diabetes rats. METHODS 8-week-old, 24 wistar & GK rats (type Ⅱ diabetes model) were randomly divided into 4 groups, NR, NE, DR, DE. Downhill running treatment were performed on the treadmill at the -16 % and speed of 16m/min for 1 hour. All groups were done with Oral glucose tolerance test(OGTT) and after 1 week washout period, rats in exercise groups performed downhill running. After exercise treatment, soleus muscle of rats were extracted for test of P-AMPK expression. RESULTS In OGTT, blood glucose levels in all groups were increased after the oral glucose load and these were significantly differ from rest level. But in DE group, blood glucose level at 120 min after OGTT was not significantly differ from rest level. In immunoblotting test for P-AMPK expression of skeletal muscle, NE group was significantly higher than NR group and DE group was significantly higher than other groups. CONCLUSIONS Downhill running exercise improved glucose tolerance and increased P-AMPK expression of skeletal muscle in type Ⅱ diabetes rats.